Physical Activity Interferes with the Immunomodulatory Effect of the Antineoplastic Drug NSC631570 - M. Skivka, Larysa; G. Fedorchuk, Olexander; M. Susak, Yaroslav; Y. Susak, Mychailo; M. Malanchuk, Oksana; P. Rudyk, Mariia; W. Nowicky, Yaroslav. (Current Pharmaceutical Biotechnology, 2015)
Objective: the aim of the work was to evaluate the effect of moderate physical exercise on the response of circulating phagocytes to the antineoplastic drug NSC 631570. Methods: Eight healthy adult men aged 23 ± 2 years were recruited to participate in the study; NSC 631570 was administered i.v. in a single therapeutic dose; blood samples were collected before and after the drug administration; the moderate physical exercise programme included 50 slow squats; total leukocyte, neutrophil and lymphocyte counts were determined using the haematological analyser; intracellular ROS generation and phagocytic activity of circulating monocytes and granulocytes were analysed by flow cytometry; PPAR-γ protein expression was evaluated by Western blot. Results: introduction of NSC 631570 in an inpatient setting was associated with a decrease in phagocyte endocytic activity along with an increase in ROS generation. Drug injection in an outpatient setting was accompanied by a significant increase in monocyte and granulocyte phagocytosis along with a decrease in the daily mean of ROS generation as well as by a decrease in monocyte reactivity reserve after stimulation in vitro. PPAR-γ expression in circulating monocytes was significantly decreased after the drug administration in an inpatient setting and was slightly increased in active participants after the drug injection. Conclusion: NSC 631570 causes M1 (N1) shift of phagocytes after in vivo introduction. Moderate physical exercise exerts a negative effect on the immunomodulatory action of NSC 631570 by abrogating M1 (N1) shift of circulating phagocytes. One of the reasons for such an effect could be an increase in PPAR-γ expression by phagocytes.
Keywords: physical exercise